Changes in Profile Characteristics Under the Influence of Bench Terracing - singh, R.K.; Mandal, S.C. (Journal of Soil and Water Conservation, 2022)
Terracing has been one of the important land management practices of the hilly regions where erosional hazards are pronounced. Chotanagpur, in Bihar, presents such problems. To tackle the problem, the farmers of this region have made indigenous types of terraces on varying soil and slope conditions. The terraced land is cropped with paddy annually and lea fallow for the rest of the year. Bench terracing is an expression of biotic factor which modifies the natural process of soil development. Cultivation and water logging further promote the changes. Literature on soil profile studies is vast and varied but adequate data on the soil profile characteristics of bench terraces are Jacking. The present study was undertaken with a view to overcoming the deficit to some extent.